Measurement of thermal influence on a two-dimensional motion trajectory using a tracking interferometer. Issue 1 (2016) - Ibaraki, S.; Blaser, P.; Shimoike, M.; Takayama, N.; Nakaminami, M.; Ido, Y.
Abstract: Conventional thermal deformation tests in ISO 230-3:2007 only measure the tool displacement when it is positioned at a single point. This paper proposes the application of a tracking interferometer to the evaluation of the thermal influence on two-dimensional motion trajectory. The full multilateration algorithm requires at least four tests repeated at different tracking interferometer positions, when only one tracking interferometer is available. This paper proposes the identification of 2D geometric errors of linear axes by single-setup tests. Since the measurement time is significantly reduced, it can be applied within a thermal test. The uncertainty analysis is also presented.